MEDICINAL PROPERTIES OF LYCHEE PLANT - Sullieva Suluv Khurramovna; Tojieva Feruza Anvarovna (Journals Park Publishing, 2022)
This article provides valuable scientific information about the Chinese lychee plant (litchi chinensis) in folk medicine, its origin and distribution area, medicinal properties, and cultivation technology.
Keywords: heat-loving, calyx, calcium, phosphorus, stem.